Effects of pervasive game on behavioral intention towards fitness among older adults in Henan: An empirical study - Erni Marlina Saari (Tanjung Malim, 2024)
Effects of pervasive game on behavioral intention towards fitness among older adults in Henan: An empirical study by Erni Marlina Saari